Experimental and numerical studies on a new type of bolt-ball joint for spatial grid structures. (January 2022) - Yang, Dabin; Li, Mingjin; Fu, Feng; Wu, Jinzhi
Abstract: The insufficient tightening due to workmanship and bolt loosen during the life cycle of spatial structures are common safety hazards in the installation process and the use stage of spatial structures. To tackle these problems, in this paper, a new type of bolt-ball joint with octagonal high-strength bolt is developed for conventional spatial structures. For this new type of node, the force was transmitted through the contact between the high-strength bolt and the inner wall of the octagonal sleeve, and the bolt is screwed into the bolt ball to avoid the shear forces on the pins. After installation, by checking whether the tail of the pin is flush with the outer surface of the sleeve, it will be easy to judge whether the high-strength bolt is properly tightened. To investigate the behavior of this new type of nodes, an experimental study on the tensile performance of octagonal high-strength bolts was performed. It is found that, the tensile strength of the octagonal high-strength bolts for this new type meets the requirements of the Chinese specification. Further detailed experimental studies and numerical simulations were carried out to investigate other nodes, namely steel-pipe, cone head/sealing plate nodes. The results show that the stress distribution and dimensions of the whole joints and the bearing capacity of the cone head are similar between the two nodes. The compressive test of the proposed new type of sleeve is also carried out, and the results show that the failure load is more than 3 times the required design value. Finally, the torsion bearing capacity test of this new type of node is carried out. The results show that the torsional bearing capacity of the new nodes during installation is much greater than that of the traditional ones. Graphical abstract: Unlabelled Image Highlights: A new type of joint system for space structure is first time invented Load resisting mechanisms of this new joint was assessed via experimental studies An analytical model was proposed to predict the load resistance of the new joint. The behavior this new joint was assessed through the experimental test and numerical analysis